التركيب النوعي لثنائيات المصراع Bivalvia في شاطئ المنشآت الصناعية في بانياس - صقر فائز; المصري محمد; صالح محمد (Latakia University Journal -Biological Sciences Series, 2019)
تم في هذا البحث دراسة التركيب النوعي لثنائيات المصراع وتغيراته في شاطئ المنشآت الصناعية في مدينة بانياس خلال الفترة الممتدة بين 15/6/ 2006 ونهاية عام 2007, حيث أظهرت النتائج أن المواقع المدروسة G, F, E, D, C, B, A" "غنية بالتركيب النوعي لثنائيات المصراع, حيث أن عدد لأنواع التي تم العثور عليها في جميع مواقع الدراسة وصل إلى 68 نوعاً. كما دلت الدراسة إلى أن الموقعين المتجاورين D,C كانا الأغنى بالأنواع, حيث وصل عدد الأنواع في كل منهما إلى 48 نوعاً , بينما كان الموقع F الأقل تنوعا" إذ بلغ عدد الأنواع فيه27 نوعاً , كما أظهرت الدراسة وجود 14 نوعاً واسعة التكيف البيئيEurybione و8 أنواع ضيقة التكيف البيئي Stenobione اقتصر وجودها على موقع واحد فقط . In this research, a study of the specific composition of Bivalvia and its diversity has been obtained, through the period between 15-06-2006 and the end of 2007, at the Industrial Plants Coast of Banyas. The results showed that the cited sites" G, F, E, D, C, B, A" were rich with specific composition of Bivalvia, and the total number of species determined at all cited sites reached up to 68 species. The study indicated that the adjacent two sites D, C were the richest with species, as the species number at the each of them was 48 species, whereas the site F was only 27 species. The study also demonstrated an existence of 14 species with high environmental adaptation Eurybione and 8 species with low environmental adaptation Stenobione, which were restricted in only one site.